Alpha-Synuclein Accumulation and Its Phosphorylation in the Enteric Nervous System of Patients Without Neurodegeneration: An Explorative Study - Bu, Lu-Lu; Huang, Kai-Xun; Zheng, De-Zhi; Lin, Dan-Yu; Chen, Ying; Jing, Xiu-Na; Liang, Yan-Ran; Tao, En-Xiang (Frontiers in Aging Neuroscience, 2020)
Alpha-synuclein (α-Syn) is widely distributed and involved in the regulation of the nervous system. The phosphorylation of α-Syn at serine 129 (pSer129α-Syn) is known to be closely associated with α-Synucleinopathies, especially Parkinson's disease (PD). The present study aimed to explore the α-Syn accumulation and its phosphorylation in the enteric nervous system (ENS) in patients without neurodegeneration. Patients who underwent colorectal surgery for either malignant or benign tumors that were not suitable for endoscopic resection (n = 19) were recruited to obtain normal intestinal specimens, which were used to assess α-Syn immunoreactivity patterns using α-Syn and pSer129α Syn antibodies. Furthermore, the sub-location of α-Syn in neurons was identified by α-Syn/neurofilament double staining. Semi-quantitative counting was used to evaluate the expression of α-Syn and pSer129α-Syn in the ENS. Positive staining of α-Syn was detected in all intestinal layers in patients with non-neurodegenerative diseases. There was no significant correlation between the distribution of α-Syn and age (p = 0.554) or tumor stage (p = 0.751). Positive staining for pSer129α-Syn was only observed in the submucosa and myenteric plexus layers. The accumulation of pSer129α-Syn increased with age. In addition, we found that the degenerative changes of the ENS were related to the degree of tumor malignancy (p = 0.022). The deposits of α-Syn were present in the ENS of patients with non-neurodegenerative disorders; particularly the age-dependent expression of pSer129α-Syn in the submucosa and myenteric plexus. The current findings of α-Syn immunostaining in the ENS under near non-pathological conditions weaken the basis of using α-Syn pathology as a suitable hallmark to diagnose α Synucleinopathies including PD. However, our data provided unique perspectives to study gastrointestinal dysfunction in non-neurodegenerative disorders. These findings provide new evidence to elucidate the neuropathological characteristics and α-Syn pathology pattern of the ENS in non-neurodegenerative conditions.